Helminth fauna of Microtus cf. arvalis (Rodentia, Cricetidae) in Russia and adjacent countries - NADEZHDA Yu. KIRILLOVA; Alexander Kirillov; ALEXANDER B. RUCHIN; MAXIM V. TRUKHACHEV (Society for Indonesian Biodiversity, 2020)
Abstract. Kirillova NYu, Kirillov AA, Ruchin AB, Trukhachev MV. 2020. Helminth fauna of Microtus cf. arvalis (Rodentia, Cricetidae) in Russia and adjacent countries. Biodiversitas 21: 1961-1979. The helminth fauna of voles of the Microtus cf. arvalis group is reviewed focusing on the Russian fauna and that of adjacent territories. In total, 61 helminth species have been recorded in these rodents: Trematoda-14, Cestoda-21, Nematoda-25, Acanthocephala-1. The diversity of the helminth community of the common vole is due to the wide species range and abundance of this rodent. M. arvalis is the final host for most of the parasites recorded from this host species. Only 10 cestodes and trematodes species use common voles as intermediate and paratenic hosts. The core of this voles’ helminth fauna is formed by common species that parasitize many different rodent species. The helminth fauna of the common vole has been most intensively studied in Russia, where 45 species of parasitic worms have been recorded in rodents. The similarity of the helminth fauna of the common vole from different study regions is determined by both the geographical proximity of the research areas and the broad distribution of most of the M. cf. arvalis helminth species.